Differences in Random Blood Glucose Levels on Acceptors of the 1-Month Injection Contraceptive Program and the 3-Month Injection Contraceptive Program in the Working Area of the Masbagik Community Health Center - Diarti, Maruni Wiwin; Mulyadi, Faiza Waziran; Pauzi, Iswari; Urip, Urip (Poltekkes Kemenkes Mataram, 2026)
Glucose is one of the products of carbohydrate metabolism in the body that functions as the main source of energy for the body, controlled by insulin. This increase in blood sugar is caused by the inefficient work of insulin, which is caused by the presence of injectable contraceptives. The progesterone hormone contained in injectable contraceptives has anti-insulin properties that cause cells to become less sensitive. Reduced insulin sensitivity can lead to insulin resistance in the body, which can affect glucose metabolism and result in elevated blood sugar levels. The objective of this study is to determine the difference in blood glucose levels among participants in the 1-month injection contraceptive program and the 3-month injection contraceptive program in the Masbagik Health Center service area. The sample in this study consisted of participants in the 1-month and 3-month injection contraceptive programs, with a total of 26 respondents (13 for each group). The data collected were glucose levels measured using the POCT (point-of-care testing) method. The data were analyzed using the Mann-Whitney statistical test. The results showed that the mean glucose level in 1-month contraceptive injection program participants was 108.8 mg/dL, while in 3-month program participants it was 142.9 mg/dL. The Mann-Whitney test results showed no significant difference between the blood glucose levels of 1-month contraceptive injection users and 3-month contraceptive injection users, with a value of 0.068 (p > 0.05). The conclusion of this study is that there is no significant difference in blood glucose levels between 1-month and 3-month contraceptive injection users. However, mathematically, there is an increase in the average values.